An efficient modified booth multiplier architecture - Razaidi, Hussin (Universiti Malaysia Perlis (UniMAP), 2012)
Multiplier plays an important role in today’s compute intensive applications such as computer graphics and digital signal processing. This thesis described the design of an Efficient Modified Booth Multiplier Architecture. With the tradeoff between speed and area, the design of the Modified Booth Multiplier focused on high speed with a moderate increase in area. This was achieved by reducing the critical path delay in the basic element of the multiplier circuit. Multiplication is performed by generating the partial product of Modified Booth Encoding (MBE) and accumulating the entire partial product by an adder or compressor. The research began by examining the available encoding schemes used to generate the partial product and 4:2 compressor that are used to accumulate the partial product. The fastest MBE and the most efficient 4:2 compressor has been used to develop the multiplier. The multiplier performance was improved by adapting various methods such as Simplified Sign Extension (SSE) and a proper tree topology. The SSE method eliminated some counter or adders in a partial product row while the tree topology arrangement of the compressors and their interconnection accumulate the partial product. A Gajski’s rule had been used to evaluate the performance of the multiplier and the result shows that the new multiplier has reduced delays in producing the output. The new multiplier architecture has reduced delays to almost 2% to 7% compared to other multipliers. The high speed multiplier was then extended to develop a Floating Point (FP) multiplier. The FP multiplier had been successfully designed using Altera Quartus II software and implemented on MAX EPM7182SLC84-7 device. The result showed that the FP multiplier is 38% faster compared to conventional FP multiplier. In term of size, the FP multiplier is 26% bigger than conventional circuit. However the increase in area of the circuit can be tolerated since the aim was to enhance the speed of the FP Multiplier